PRAGMATIC COMPETENCE OF TEACHER-STUDENTS AT ENGLISH EDUCATION DEPARTMENT - Nunung Nurjati; Ferra Dian Andanty (LPPM Universitas PGRI Adi Buana Surabaya, 2016)
English in Indonesia is still acting as a foreign language in a way that the language is still limited in use to be practiced in schools. English has not been as a second language in Indonesia. As a foreign language, English is still not fully utilized as appropriate in countries native speakers. The L2 still encounter verbal interaction with speakers of foreign languages, especially English teachers and learners in schools that are not in accordance with the function and the situation. The purposes of this study are to (1) describe the utterances used by the lecturer-student in meaningful situation, and (2) to describe a form of speech which implies related to the competence of pragmatic form of representation of (1) deixis, (2) conversational implicatures, (3) pre-supposition, and (4) acts of speech in the discourse of learning instructional interaction in English language education courses. This study uses a qualitative approach to the narrative definition. The data of this study include: (1) verbal aspects of speech acts between lecturer and students situational context, and (2) a form of speech acts that implies in terms of illocutionary and in terms of conversational implicatures. Keywords: pragmatic competence, situational meaning, narrative definition, deixis, conversational implicatures